Abstract 130: Endovascular Therapy for Cerebral Venous Sinus Thrombosis: A Systematic Review of 267 patients - Abdullah Sultany; Abdullah M. Al Qudah; Guvanch Kakamyradov; Mohamed F. Doheim (Stroke: Vascular and Interventional Neurology)
Introduction Cerebral venous sinus thrombosis (CVST) is a rare form of stroke that usually affects young females especially during pregnancy and the postpartum period. Several risk factors can contribute to the development of cerebral venous sinus thrombosis including hypercoagulable states, dehydration, infections, head or neck injuries, cancer, and some rheumatological diseases (1). The symptoms of cerebral venous sinus thrombosis can vary depending on the location and extent of the clot. Common signs and symptoms may include severe headaches, visual disturbances, seizures, focal neurological deficits, altered mental status, and in severe cases, coma. The initial treatment for CVST is systemic anticoagulation (2‐3). However, endovascular treatment (EVT) of CVST is typically reserved for cases associated with significant thrombus burden and lack of clinical improvement or worsening of symptoms despite systemic anticoagulation therapy without current conclusive evidence of its benefit. The aim of this study is to evaluate the evidence of EVT in patients with CVST. Methods A systemic literature search was conducted via PubMed to identify relevant studies. Only studies with sample sizes larger than 10 were included. We excluded small case series, meta‐analyses, systematic reviews, and studies that lack the main outcomes of interest. Our main outcomes included functional outcome defined as modified Rankin Scale score (mRS 0‐3), mortality, new or expanded ICH and recanalization rates. Results We finally included 10 studies (4‐13) in our qualitative synthesis. Only one study was a small, randomized clinical trial while the rest were observational studies. In our included studies, 267 patients underwent EVT for CVST. Among them, the median age was ranging from 12 to 75 and 162 (60 %) of patients were females. Patients were followed up for a mean ranging from 3 to 12 months. Recanalization was observed in 161 patients, out of which 111 were complete recanalization (68.9%) and 50 were partial recanalization (31.1%). Good functional outcome defined as mRS 0‐3 was achieved in a total of 181 patients. Additionally, 26 (9.7%) patients had a new onset or expanded ICH while 26 patients had died (9.7%). Conclusion EVT for CVST was associated with improved clinical outcomes with acceptable safety profile in severe cases. There is a lack of evidence from large randomized clinical trials so more prospective studies are needed to confirm these results.